Teachers’ Practices and Students’ Perceptions on Feedback - Mani Ram Sharma; Shiv Ram Pandey (Ñemitỹrã, 2024)
This article presents ideas on Teachers’ Practices and Students’ Perceptions on feedback. The main objective of this study was to explore the practices of providing feedback in the semester classes of Master’s in English Education. It has tried to find out the perceptions of the students on the role of feedback in their learning. Case study research design was used in this study. To meet the set objectives, 2 teachers and 4 students from M.Ed. first semester, Department of English Education, Gramin Adarsha Multiple Campus were selected using purposive sampling strategy. Open-ended questionnaire and observation were used as the main tools for eliciting the required information. Besides, researcher’s own diary and experiences were used to take notes of specific cases which were not included in the observation. From the analysis of data and interpretation of the results, it was found that the teachers practiced correcting as the common way of providing feedback to the students. Similarly, the students perceived feedback as an information provided to the learners with the objective of improving their performance. They said that feedback played a constructive and catalytic role in their learning. Teachers’ feedback worked as a motivation tool in the process of teaching and learning.